PENERAPAN STRATEGI PEMBELAJARAN AFEKTIF DALAM PEMBELAJARAN UNGGAH-UNGGUH BAHASA JAWA DI SEKOLAH DASAR - Akbar Al Masjid (Universitas Sarjanawiyata Tamansiswa, 2016)
Politeness language or commonly called the speech level in the society until now still held fast by the user community. However, the younger generation are now starting to use the Java language difficulties diverse of manners. This implies that the values of decency that became the pride of the Java community today has become even more faded. Based on the authors provide solutions in an effort to increase the upload-ungguh skills using the Java language through affective learning strategies. The technique using the technique of habituation and modeling techniques.